KAJIAN YURIDIS PENERAPAN UNDANG-UNDANG NO. 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSISTEMNYA (Kajian terhadap Putusan Nomor : 82 / Pid.Sus / 2015 / PN.Skt) - ASTUTI, UJI (Dinamika Hukum, 2017)
The purpose of this study is to analyze the judges' considerations in Decision No.82 / Pid.Sus / 2015 / PN.Skt and analyzed the relationship between judges'considerations and efforts to conserve biological natural resources.The background of research that conservation of biological natural resources isimportant because law enforcement against violation of Law no. 5 of 1990Concerning the Conservation of Biological Natural Resources and Ecosystem isan effort to conserve the animals protected by the law.The research method includes the type of research in the form of normativejuridical because only menaganalisis secondary data in the form of law and judgedecision. The nature of descriptive research and data analysis is done normativelyqualitative.The result of the research shows that Decision Number 82/Pid.Sus /2015 /PN.Sktwhich impose the imprisonment and fine against the defendant violating Law No.5 of 1990 concerning Conservation of Biological Natural Resources and itsEcosystem is a form of law enforcement protecting biological natural resources inthis form of green turtle species. Such protection efforts are manifested in thedecision of a judge in the form of a cumulative criminal (imprisonment and fine).There is also a consideration about the criminal incriminating act of defendantdoes not succeed in government programs in maintaining protected animals.Keywords: Judicial Review, Decision No.82 / Pid.sus / 2015 / PN Skt, Law No.5of 1990 on Conservation of Biological Natural Resources and Ecosystem